Implementation of Training Design to Improve Teacher Competence Based on Googleform Journal Teacher Agenda in SMPN 27 Pesawaran - Sari, Melian; Firdaus, Rangga; Riswandi, Riswandi (UNDIKMA, 2024)
Professional teachers are the main determinants of educational success. One indicator of teacher professional competence is the ability to manage teaching and learning programs using the use of information technology. The reality of teacher professionalism in the learning process at this time is still diverse, one of which is that teachers have not been able to show good performance. To measure teacher performance, supervision is carried out by the principal, as one of the steps to monitor and provide direct follow-up on the teacher's performance. Based on the findings of the researchers, it is known that the inability of teachers to show good performance is influenced by the lack of information, design, implementation in improving the professional performance of teachers, especially in teacher competencies based on google form, for this reason teacher competency training is needed. This research uses the method method (SLR). regarding research methods: